Odontogenic Tumors: A Challenge for Clinical Diagnosis and an Opportunity for AI Innovation - Mohammad Reza Golzar Feshalami; Mehraban Shahi; Nasrin Davaridolatabadi (Shiraz University of Medical Sciences, 2024)
The advancement of artificial intelligence (AI) has opened up new possibilities for medical diagnosis and treatment. In particular, AI algorithms have demonstrated remarkable potential in analyzing patient radiology images and histopathological samples, offering insights that can enhance clinical decision-making [1]. This letter explores the emerging role of AI in the diagnosis and treatment of odontogenic tumors (OTs), a group of benign, malignant, and tumor-like malformations arising from the remnants of the tooth-forming apparatus.